2018
DOI: 10.1093/geronb/gby071
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan Socioeconomic Context: Associations With Cognitive Functioning in Later Life

Abstract: Independent of current SES, childhood and adulthood SEC predicted later-life cognition, which may be sensitive to effects of social institutions and environmental health. SEC assessed across the lifespan, and related residential mobility information, may be important complements to SES in predicting later-life cognitive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…These associations remained after adjusting for family SES or largely remained after adjusting for perceptions of neighborhood safety. Thus, these social disparities merit further study to assess their prospective role in increasing developmental disparities in health and mental health and in the differences in neurocognition and brain structure in adulthood . These associations were largely consistent across 21 US metropolitan areas, suggesting a widespread and potentially generalizable pattern.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These associations remained after adjusting for family SES or largely remained after adjusting for perceptions of neighborhood safety. Thus, these social disparities merit further study to assess their prospective role in increasing developmental disparities in health and mental health and in the differences in neurocognition and brain structure in adulthood . These associations were largely consistent across 21 US metropolitan areas, suggesting a widespread and potentially generalizable pattern.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, these social disparities merit further study to assess their prospective role in increasing developmental disparities in health and mental health [15][16][17]79 and in the differences in neurocognition and brain structure in adulthood. [80][81][82][83][84][85] These associations were largely consistent across 21 US metropolitan areas, suggesting a widespread and potentially generalizable pattern. Moreover, associations were primarily attributed to the local variation in neighborhood disadvantage within metropolitan areas.…”
Section: Discussionmentioning
confidence: 92%
“…This result does not agree with previous findings as the economically disadvantaged group was expected to obtain lower scores [ 30 ]. A previous study which examined how early ages’ Socioeconomic Context (SEC) affects cognitive functions throughout an entire life span [ 76 ], showed that higher SECs in early ages and adulthood were related to better scores in verbal memory recognition. The literature regarding memory of participants with a background of poverty shows a link between lower family income and the hypo-reactivity of the cortisol response, which has been shown to be linked to associative memory in children [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were derived from an imaging sub-study of a longitudinal cohort study on self-regulation, brain, and cognitive health in older adults (D. R. Evans & Segerstrom, 2015; Geiger et al, 2019; Scott et al, 2019; Segerstrom et al, 2022). To be eligible, participants had to be 60 years or older and nonsmokers.…”
Section: Methodsmentioning
confidence: 99%